An optimal control for complete synchronization of 4D Rabinovich hyperchaotic systems - Shaymaa Y. Al-Hayali; Saad Fawzi Al-Azzawi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This paper derives new results for the complete synchronization of 4D identical Rabinovich hyperchaotic systems by using two strategies: active and nonlinear control. Nonlinear control strategy is considered as one of the powerful tool for controlling the dynamical systems. The stabilization results of error dynamics systems are established based on Lyapunov second method. Control is designed via the relevant variables of drive and response systems. In comparison with previous strategies, the current controller (nonlinear control) focuses on convergence speed and the minimum limits of relevant variables. Better performance is to achieve full synchronization by designing the control with fewer terms. The proposed control has certain significance for reducing the time and complexity for strategy implementation.